Nontraumatic Hemobilia in Children - Anjana Bairagi; Daniel C. Aronson (Georg Thieme Verlag KG, 2015)
Abstract Nontraumatic hemobilia is a rare cause of upper gastrointestinal hemorrhage in children. In the developing world, infections and inflammation are the two most common causes. Two patients are presented illustrating the diagnostic difficulties. Following recognition of the site of bleeding the surgery was successful in each case. After a review of the literature, a diagnostic workup is proposed.